A Rapid High Throughput Vibration and Vortex-Assisted Matrix Solid Phase Dispersion for Simultaneous Extraction of Four Isoflavones for Quality Evaluation of Semen Sojae Praeparatum - Yang, Xuejing; Sun, Ali; Boadi, Evans Owusu; Li, Jin; He, Jun; Gao, Xiu-mei; Chang, Yan-xu (Frontiers in Pharmacology, 2020)
Isoflavones (daidzein, daidzin, genistein and genistin) were main chemical components and usually selected as markers for quality control of Traditional Chinese Medicine semen sojae praeparatum (SSP). High throughput vibration and vortex-assisted matrix solid phase dispersion and high performance liquid chromatography with diode array detection were developed to simultaneously extract and quantify four isoflavones in SSP. Some parameters influencing extraction efficiency of isoflavones by vortex-assisted matrix solid phase dispersion such as sorbent type, ratio of sample to sorbent, crushing time, vibration frequency, methanol concentration, eluting solvent volume and vortex time were optimized. It was found that the best extraction yields of four isoflavones were obtained when the sample (20 mg) and SBA-3 (40 mg) was crushed by ball mill machine for 2 min at vibration frequency of 800 times per minute. Methanol/water (1.5 ml, 8:2, v/v) solution was dropped into the treated sample and vortexed for 3 min. The recoveries of the four isoflavones ranged from 86.1 to 94.8% and all relative standard deviations were less than 5%. A good linearity (r > 0.9994) was achieved within the range 0.5–125 μg/ml. It was concluded that the high throughput vibration and vortex-assisted matrix solid-phase dispersion coupled with high performance liquid chromatography was user-friendly extraction and quantification method of multiple isoflavones for quality evaluation of SSP.